Cellular, mitochondrial and molecular alterations associate with early left ventricular diastolic dysfunction in a porcine model of diabetic metabolic derangement - Ilkka Heinonen; Oana Sorop; Bas M. van Dalen; Rob C. I. Wüst; Jens van de Wouw; Vincent J. de Beer; Yanti Octavia; Richard W. B. van Duin; Youri Hoogstrate; Lau Blonden; Milla Alkio; Katja Anttila; et al. (NATURE RESEARCH, 2022)
The prevalence of diabetic metabolic derangement (DMetD) has increased dramatically over the last decades. Although there is increasing evidence that DMetD is associated with cardiac dysfunction, the early DMetD-induced myocardial alterations remain incompletely understood. Here, we studied early DMetD-related cardiac changes in a clinically relevant large animal model. DMetD was established in adult male Gottingen miniswine by streptozotocin injections and a high-fat, high-sugar diet, while control animals remained on normal pig chow. Five months later left ventricular (LV) function was assessed by echocardiography and hemodynamic measurements, followed by comprehensive biochemical, molecular and histological analyses. Robust DMetD developed, evidenced by hyperglycemia, hypercholesterolemia and hypertriglyceridemia. DMetD resulted in altered LV nitrosoredox balance, increased superoxide production-principally due to endothelial nitric oxide synthase (eNOS) uncoupling-reduced nitric oxide (NO) production, alterations in myocardial gene- expressionparticularly genes related to glucose and fatty acid metabolism- and mitochondrial dysfunction. These abnormalities were accompanied by increased passive force of isolated cardiomyocytes, and impaired LV diastolic function, evidenced by reduced LV peak untwist velocity and increased E/e'. However, LV weight, volume, collagen content, and cardiomyocyte cross-sectional area were unchanged at this stage of DMetD. In conclusion, DMetD, in a clinically relevant large-animal model results in myocardial oxidative stress, eNOS uncoupling and reduced NO production, together with an altered metabolic gene expression profile and mitochondrial dysfunction. These molecular alterations are associated with stiffening of the cardiomyocytes and early diastolic dysfunction before any structural cardiac remodeling occurs. Therapies should be directed to ameliorate these early DMetD-induced myocardial changes to prevent the development of overt cardiac failure.